1999
DOI: 10.1016/s0022-5347(01)61607-0
|View full text |Cite
|
Sign up to set email alerts
|

5-Year Followup of a Randomized Prospective Study Comparing Mitomycin C and Bacillus Calmette-Guerin in Patients With Superficial Bladder Carcinoma

Abstract: Therapy with BCG was superior to mitomycin C for recurrence prophylaxis but no difference was found for progression and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
2
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(81 citation statements)
references
References 14 publications
0
74
2
5
Order By: Relevance
“…Malmstrom et al looked at MMC in patients who had failed BCG and reported a 19% 3-year disease-free rate among intermediate and high-risk patients. 141 Valrubicin, a semisynthetic analog of doxorubicin and lipid soluble anthracycline, has demonstrated antitumor activity in nonmuscle-invasive bladder cancer and was evaluated as treatment for patients with CIS who failed BCG treatment. 142 Ninety patients with recurrent CIS after BCG failure were given 6 weekly instillations of 800 mg of intravesical valrubicin; 21% of patients initially had a complete response, but at a median follow up of 30 months, 88% of patients recurred, and 56% of these patients went on to have a radical cystectomy of which 15% had pT3 disease at time of surgery.…”
Section: Nonmuscle-invasive Diseasementioning
confidence: 99%
“…Malmstrom et al looked at MMC in patients who had failed BCG and reported a 19% 3-year disease-free rate among intermediate and high-risk patients. 141 Valrubicin, a semisynthetic analog of doxorubicin and lipid soluble anthracycline, has demonstrated antitumor activity in nonmuscle-invasive bladder cancer and was evaluated as treatment for patients with CIS who failed BCG treatment. 142 Ninety patients with recurrent CIS after BCG failure were given 6 weekly instillations of 800 mg of intravesical valrubicin; 21% of patients initially had a complete response, but at a median follow up of 30 months, 88% of patients recurred, and 56% of these patients went on to have a radical cystectomy of which 15% had pT3 disease at time of surgery.…”
Section: Nonmuscle-invasive Diseasementioning
confidence: 99%
“…Mitomycin, epidoxorubicin and doxorubicin have all shown to have beneficial effects, but the optimal instillation scheme remains to be defined (Malmstrom et al, 1999;Malmstrom, 2000). Similarly, the best treatment for patients who fail to respond to adjuvant intravesical treatment needs further investigation, but cytotoxic drugs could represent an interesting alternative to standard BCG therapy.…”
mentioning
confidence: 99%
“…After an extensive preclinical evaluation and marker lesion study, two phase III trials evaluated the immediate use of apaziquone following TURBT for Ta/T1 disease. [40] These studies were designed to detect a 12% absolute difference between apaziquone and placebo in the primary endpoint (2-year recurrence rate) at 5% level of significance and powered at 80%. However, both trials with 6.6% (SPI-611) and 6.2% (SPI-612) reductions in recurrence rates when compared with the placebo groups failed to achieve this outcome.…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%